Historical Dialogue Analysis - Jucker, Andreas H.,Fritz, Gerd,Lebsanft, Franz (John Benjamins Publishing Company, 1999)
Historical dialogue analysis is a new branch of historical pragmatics. The papers of this interdisciplinary volume contribute to charting the developing field by presenting a survey of recent research from the different traditions of English, German and Romance language studies. Both the introductory paper by the editors and the individual papers deal with fundamental theoretical questions, e.g. the question of types of historical developments in dialogue forms, and methodological problems, e.g. the finding and interpretation of relevant data. The fifteen case studies presented in this volume provide a wide range of new data. The range of topics includes the pragmatic form of 16th century religious controversies in Germany, forms of polite answers in Early Modern German conversation culture, forms of dialogue in Early Modern English medical writing, learning English through dialogues in the 16th century, structures of bargaining dialogues in Late Medieval French, and reflections of spontaneous dialogue in Early Romance texts.
Description based on publisher supplied metadata and other sources
Keywords: Dialog; Konversationsanalyse; Historische Sprachwissenschaft